The healthiness and sustainability of national and global food based dietary guidelines: modelling study. (15th July 2020) - Springmann, Marco; Spajic, Luke; Clark, Michael A; Poore, Joseph; Herforth, Anna; Webb, Patrick; Rayner, Mike; Scarborough, Peter
Abstract: Objective: To analyse the health and environmental implications of adopting national food based dietary guidelines (FBDGs) at a national level and compared with global health and environmental targets. Design: Modelling study. Setting: 85 countries. Participants: Population of 85 countries. Main outcome measures: A graded coding method was developed and used to extract quantitative recommendations from 85 FBDGs. The health and environmental impacts of these guidelines were assessed by using a comparative risk assessment of deaths from chronic diseases and a set of country specific environmental footprints for greenhouse gas emissions, freshwater use, cropland use, and fertiliser application. For comparison, the impacts of adopting the global dietary recommendations of the World Health Organization and the EAT-Lancet Commission on Healthy Diets from Sustainable Food Systems were also analysed. Each guideline's health and sustainability implications were assessed by modelling its adoption at both the national level and globally, and comparing the impacts to global health and environmental targets, including the Action Agenda on Non-Communicable Diseases, the Paris Climate Agreement, the Aichi biodiversity targets related to land use, and the sustainable development goals and planetary boundaries related to freshwater use and fertiliser application. Results: Adoption of national FBDGs was associated with reductions in premature mortality of 15% on average (95% uncertainty interval 13% to 16%) and mixed changes in environmental resource demand, including a reduction in greenhouse gas emissions of 13% on average (regional range −34% to 35%). When universally adopted globally, most of the national guidelines (83, 98%) were not compatible with at least one of the global health and environmental targets. About a third of the FBDGs (29, 34%) were incompatible with the agenda on non-communicable diseases, and most (57 to 74, 67% to 87%) were incompatible with the Paris Climate Agreement and other environmental targets. In comparison, adoption of the WHO recommendations was associated with similar health and environmental changes, whereas adoption of the EAT-Lancet recommendations was associated with 34% greater reductions in premature mortality, more than three times greater reductions in greenhouse gas emissions, and general attainment of the global health and environmental targets. As an example, the FBDGs of the UK, US, and China were incompatible with the climate change, land use, freshwater, and nitrogen targets, and adopting guidelines in line with the EAT-Lancet recommendation could increase the number of avoided deaths from 78 000 (74 000 to 81 000) to 104 000 (96 000 to 112 000) in the UK, from 480 000 (445 000 to 516 000) to 585 000 (523 000 to 646 000) in the USA, and from 1 149 000 (1 095 000 to 1 204 000) to 1 802 000 (1 664 000 to 1 941 000) in China. Conclusions: This analysis suggests that national guidelines could be both healthier and more sustainable. Providing clearer advice on limiting in most contexts the consumption of animal source foods, in particular beef and dairy, was found to have the greatest potential for increasing the environmental sustainability of dietary guidelines, whereas increasing the intake of whole grains, fruits and vegetables, nuts and seeds, and legumes, reducing the intake of red and processed meat, and highlighting the importance of attaining balanced energy intake and weight levels were associated with most of the additional health benefits. The health results were based on observational data and assuming a causal relation between dietary risk factors and health outcomes. The certainty of evidence for these relations is mostly graded as moderate in existing meta-analyses.